2021
DOI: 10.1002/path.5675
|View full text |Cite
|
Sign up to set email alerts
|

Modelling hereditary diffuse gastric cancer initiation using transgenic mouse‐derived gastric organoids and single‐cell sequencing

Abstract: Hereditary diffuse gastric cancer (HDGC) is a cancer syndrome caused by germline variants in CDH1, the gene encoding the cell–cell adhesion molecule E‐cadherin. Loss of E‐cadherin in cancer is associated with cellular dedifferentiation and poor prognosis, but the mechanisms through which CDH1 loss initiates HDGC are not known. Using single‐cell RNA sequencing, we explored the transcriptional landscape of a murine organoid model of HDGC to characterize the impact of CDH1 loss in early tumourigenesis. Progenitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…As the most promising biotechnology de ned by Nature Methods in 2013, single-cell sequencing shows superior advantages in the identi cation of inter-tumoral heterogeneity and intra-tumoral heterogeneity recent years [15,16]. Actually, single-cell sequencing has already been applied to investigate the heterogeneity in gastric cancer and speci c genes have been identi ed to be responsible for the malignance of gastric cancer, such as OR51E1 [17], Gkn3 [18], and Krt7 [19].…”
Section: Discussionmentioning
confidence: 99%
“…As the most promising biotechnology de ned by Nature Methods in 2013, single-cell sequencing shows superior advantages in the identi cation of inter-tumoral heterogeneity and intra-tumoral heterogeneity recent years [15,16]. Actually, single-cell sequencing has already been applied to investigate the heterogeneity in gastric cancer and speci c genes have been identi ed to be responsible for the malignance of gastric cancer, such as OR51E1 [17], Gkn3 [18], and Krt7 [19].…”
Section: Discussionmentioning
confidence: 99%
“…SCS helps to clarify the molecular level mechanism of the immune cells in the tumor microenvironment during tumor cell generation, development, metastasis, drug resistance and immune escape. It contributes to a more accurate clinical diagnosis, treatment, and prognosis of solid tumors ( 19 , 20 ). In the past few years, several researchers have made significant advances in microenvironmental research by using SCS to analyze GC cells ( Table 2 ).…”
Section: Scs Applications and Achievements In Gcmentioning
confidence: 99%
“…Analysis of the SCS data from mice with hereditary diffuse gastric cancer (HDGC) revealed that inactivation of Cdh1 led to metastasis along the squamous cell differentiation trajectory associated with aberrant expression of GI epithelial differentiation center genes. Cytokeratin 7 encoded by the differentiation-dependent gene Krt7, was a specific marker of early neoplastic lesions in CDH1 carriers ( 20 ). In conclusion, SCS is valuable in identifying prognostic tumor markers for predicting potential clinical outcomes and immune responses, as well as, for individualized therapy.…”
Section: Scs Applications and Achievements In Gcmentioning
confidence: 99%
“…Moreover, TME-specific helper T cells, cytotoxic T cells, Tregs, and NK cells were found to express multiple immune checkpoint and costimulatory molecules ( 58 ). In addition, CDH1 loss resulted in shifts along the squamous differentiation trajectory, as well as the aberrant expression of the KRT7 gene (encoding the CK7 protein), which was identified as the top candidate leading to gastrointestinal epithelial invasion and early metastasis in CDH1 carriers ( 59 ). Chromatin accessibility has been identified as one of the most relevant genomic characteristics associated with oncologic functions at a specific site, providing the structure for transcription TFs binding to regulate multiple genes, thus driving cancer progression and invasion ( 60 ).…”
Section: Single-cell Sequencing In Cancer: Lessons Learnedmentioning
confidence: 99%